Possibilities for the development of rural tourism – Senj and its surroundings - Rajković, Marijeta (2007)
Based on the result of research conducted within the project 'Identity and Ethno-genesis of Coastal Bunjevci' the authors present the traditional heritage of the Senj hinterland. They point to the applicability of ethnologic research in the development of rural tourism and to the revitalization of this region through sustainable development. The authors single out the following segments: traditional economy, traditional architecture, transport, water supply, textile manufacturing, traditional cuisine, and folk medicine. Based on the presented results they conclude that the micro-region abounds in natural and anthropogenous attraction resources. They give guidelines to relate the resources of rural tourism, in the form of an ethno-museum, with the already designed tourist offer of the town of Senj, as a contribution to enriching the present tourist offer.